Effect of Maternal Body Mass Index on Postpartum Hemorrhage. (April 2018) - Butwick, Alexander J.; Abreo, Anisha; Bateman, Brian T.; Lee, Henry C.; El-Sayed, Yasser Y.; Stephansson, Olof; Flood, Pamela
Abstract : Background: It is unclear whether obesity is a risk factor for postpartum hemorrhage. The authors hypothesized that obese women are at greater risk of hemorrhage than women with a normal body mass index. Methods: The authors conducted a cohort study of women who underwent delivery hospitalization in California between 2008 and 2012. Using multilevel regression, the authors examined the relationships between body mass index with hemorrhage (primary outcome), atonic hemorrhage, and severe hemorrhage (secondary outcomes). Stratified analyses were performed according to delivery mode. Results: The absolute event rate for hemorrhage was 60, 604/2, 176, 673 (2.8%). In this cohort, 4% of women were underweight, 49.1% of women were normal body mass index, 25.9% of women were overweight, and 12.7%, 5.2%, and 3.1% of women were in obesity class I, II, and III, respectively. Compared to normal body mass index women, the odds of hemorrhage and atonic hemorrhage were modestly increased for overweight women (hemorrhage: adjusted odds ratio [aOR], 1.06; 99% CI, 1.04 to 1.08; atonic hemorrhage: aOR, 1.07; 99% CI, 1.05 to 1.09) and obesity class I (hemorrhage: aOR, 1.08; 99% CI, 1.05 to 1.11; atonic hemorrhage; aOR, 1.11; 99% CI, 1.08 to 1.15). After vaginal delivery, overweight and obese women had up to 19% increased odds of hemorrhage or atonic hemorrhage; whereas, after cesarean delivery, women in any obesity class had up to 14% decreased odds of severe hemorrhage. Conclusions: The authors' findings suggest that, at most, maternal obesity has a modest effect on hemorrhage risk. The direction of the association between hemorrhage and body mass index may differ by delivery mode. Abstract : Obesity was not found to be a strong risk factor for postpartum hemorrhage.